PERENCANAAN DAN PEREKRUTAN SUMBER DAYA MANUSIA ABAD 21 - Hadi Samanto (ITB AAS INDONESIA, 2015)
In the 21st century, competition for professional workforce is very strict because companies want a workforce that can work efficiently. So the company is very concerned about manpower planning for the foreseeable future. Recruitment of personnel can be done from within the organization or from outside the organization. Resource planning is the process of anticipating and making labor movement tools in and out of the organization, as well as guidelines for the organization's leadership and a series of changes to the recruitment plan. Changes in manpower planning are very influential not only in recruitment of labor but also in methods of selection, training, compensation and motivation. Organizational planning for the future is primarily concerned with manpower planning. First, human resources are closely linked to the process chain of planning, mapping the shape of an organization in which humans as models and ensuring familiarity and flexibility. Second, managers must follow a systematic model when undertaking a work plan. The situation is much related to labor demand forecasting, labor supply forecasting, and recruitment within the organization., Third, recruitment within the organization can come from within the organization and from outside the organization.